Endothelial Microvascular Dysfunction and Its Relationship with Haptoglobin Levels in Patients with Different Phenotypes of Chronic Heart Failure - V. I. Podzolkov; N. A. Dragomiretskaya; I. G. Beliaev; Ju. S. Kucherova; A. V. Kazadaeva (Столичная издательская компания, 2021)
Aim. To study the relationship between the level of haptoglobin and the main indicators of microcirculation (MC) in patients with different phenotypes of chronic heart failure (CHF).Materials and methods. Patients with different phenotypes of functional class II-IV chronic heart failure according to NYHA (n=80) underwent a general clinical examination, determination of the serum haptoglobin level by enzyme-linked immunosorbent assay, as well as an assessment of the MC state on the medial surface of the upper third of the leg by laser Doppler flowmetry (LDF).Results. Patients with CHF included patients with preserved left ventricular ejection fraction (HFpEF; n=27, intermediate ejection fraction (HFmrEF; n=25) and reduced ejection fraction (HFrEF; n=28). The median value of haptoglobin in the HFpEF group was 1387.6 [ 747.5; 1946.9] mg/l, in the HFmrEF group was 1583.4 [818.9; 2201.4] mg/l, in the HFrEF group was 968.5 [509.5; 1324.4] mg/l. Correlation analysis revealed statistically significant relationships between haptoglobin and the amplitudes of the endothelial frequency range (Ae) in the groups of HFmrEF (r=-0.628, 95% confidence interval [CI] -0.256; -0.825, p=0.003) and HFrEF (r=-0.503, 95% CI -0.089; -0.803, p=0.02). A negative relationship between the haptoglobin level and Kv and σ was revealed, as well as a formula for calculating the value of haptoglobin was obtained, which is predicted on the basis of the amplitude index of the endothelial frequency range: [haptoglobin]=1787-(4053×Ae).Conclusion. The multifactorial effect of haptoglobin is realized in the central and peripheral mechanisms of MC regulation. Low values of haptoglobin in blood plasma should be considered as a potential marker for the development of complications and used in a comprehensive assessment of the state of patients with CHF. Evaluation of the diagnostic and prognostic significance of haptoglobin, especially in patients with HFmrEF, requires further study.